Iron-Manganese Bimetallic-Organic Framework as A Photocatalyst for Degradation of Rhodamine B Organic Dye Under Visible Light - Tran Thi Kim Ngan; Tran Bich Thuy; Lam Van Tan; Trung Thanh Nguyen (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
In recent years, there have been many research works on use of different methods to treat textile dyeing wastewater such as mechanical, biological and chemical methods (using oxidizing agents, such as: H2O2, O3, and H2O2/O3). However, some traditional textile dyeing wastewater treatment methods such as mechanical and biological methods have limitations in treating these pollutants thoroughly. To enhance the treatment efficiency, the use of photocatalysts combination with strong oxidizing agents, such as H2O2, has been extensively developed in recent years. In this study, the iron-centred bimetallic organic framework Fe-MOF has been synthesized by partial replacement of Fe3+ ions with Mn metal ions by solvent-thermal method. The analytical methods used to evaluate the structural characterization of the as-synthesized materials including Scanning Electron Microscope (SEM), Brunaurer-Emmett-Teller (BET), X-ray Diffraction (XRD), Fourier Transform Infra Red (FT-IR), and UV-Vis Diffuse Reflectance Spectroscopy (DRS). The experiments on the decomposition of organic pigment Rhodamine B were performed under varying conditions of pH, catalyst mass and RhB colorant concentration. Experiments with different electron capturers indicate that h+ plays a major role in the photochemical degradation of RhB. The stability and durability of the 0.1 Mn/Fe-MOF catalyst were evaluated through the leaching and recycle experiments, showing that the RhB degradation efficiency of the photocatalyst decreased modestly after five repetitions. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).